Policies Relating to Criminal Economic Law to Overcome the Covid-19 Pandemic and Analysis of Their Impact on Indonesia's Statement out of the Crisis after China - Farkhan Junaedi; John Franky Yanafia Ariandi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Covid-19 has been developing in Indonesia for more than six months. This situation is to take advantage of opportunities for personal gain. These things are mainly related to the economy. The government has committed more than 150,000 cases of economic crime and also sold 160,000 cases of basic food and medical equipment. The Indonesian government is taking wise steps in overcoming the economy during this pandemic. The government issued nine policies that have been implemented some time ago until now. These things are regulated in Government Regulation in place of the Constitution of the Republic of Indonesia Number 1 of 2020. The impact of the policies provided by the government is undoubtedly tremendous for the people of Indonesia. This policy can undoubtedly help Indonesia to escape from the economic crisis quickly.